MEDIA DIGITAL YOUTUBE DALAM PEMBELAJARAN BUDAYA INDONESIA BAGI PEMELAJAR BIPA A1 THAMMASAT UNIVERSITY THAILAND - Hasnah Setiani (Jurnal Bastra (Bahasa dan Sastra), 2025)
The type of media that can be applied is YouTube digital media in introducing Indonesian culture to BIPA students. This research aims to describe the implementation of YouTube media which contains Banyumasan Arts and Tourist Attractions in Indonesia in cultural learning for BIPA level A1 students at Thammasat University, Thailand. The method used in this research is descriptive qualitative research media. Based on research results, YouTube media is very effective in introducing culture to foreign students and makes it easier for teachers to convey learning material to foreign students, especially foreign students learning Indonesian, which is a second language. The benefits of using YouTube digital media are creating communicative, interesting learning, minimizing the translation process in learning, encouraging students to actively explore during learning, and being a stimulus that can improve language skills including listening, reading, speaking and writing.